THEMATIC CONTENT FEATURES OF THE COURSE "INFORMATION TECHNOLOGIES" FOR STUDENTS OF ENVIRONMENTAL SPECIALTIES (Journal of Information Technologies in Education (ITE), 2013)
Specifics of formation of professional competence for the students of an ecological profile (in a context of possession by modern technologies of information processings) is considered. The estimated themes and the content of some teaching sessions of a course «Information technologies»for students of specialty «Ecology and environmental protection» is offered.
Keywords: educational module; information technologies; ecological information; geoinformation systems